The Role of the Notary in the Unilateral Cancellation of the Deed of Land Sale and Purchase Agreement Due to Default and the Legal Consequences - Pradifta, Admyral Argha (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Notary as a public official with the authority to make or cancel an agreement, in this case a land sale and purchase agreement. The cancellation of an agreement unilaterally can be caused by a breach of contract or default by the parties. This certainly causes losses for interested parties. It is known that this study uses a normative yiridis method with a statutory approach, namely provisions related to the position of a notary who are associated with the concept of a land sale and purchase binding agreement and its legal consequences. In the discussion, it is known that the unilateral cancellation of the binding agreement for the sale and purchase of land on the basis of breach of contract or default is an act that is not against the law. The Notary based on his authority is obliged to ask for an explanation from the canceling party and the party deemed to have committed a breach of contract or default to discuss the legal consequences of the cancellation. Next is the process of canceling the binding agreement on the sale and purchase of land which is marked by the deletion from the list of deeds belonging to the Notary.